PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE MOOD, UNDERSTAND, RECALL, DIGEST, EKSPAND, REVIEW TERHADAP PEMAHAMAN KONSEP DALAM PEMBELAJARAN MATEMATIKA SMP PEMBANGUNAN LABORATORIUM UNP - Hasanah, Rafika Ulfa (Departemen Matematika, 2023)
Understanding mathematics concepts is a fundamental goal to be achieved while learning mathematics. However, based on data from daily assessment results of the 'Relations and Functions' teaching material, it was found in the field that understanding of mathematical concepts was still low among his 8th grade students at SMP Pembangnan Laboratorium UNP. His one solution to overcome this problem is to use collaborative learning models for Mood, understanding, recalling, detersion, engaging and validating. The purpose of this study is to show that students' understanding of mathematical concepts using a MURDER-type collaborative learning model is superior to that of students using a direct learning model in Class 8th at the SMP Pembangnan Laboratorium UNP. It was about knowing if it was better than understanding. This type of study is quasi-experimental with a quasi-experimental study design. Sample selection was performed by a simple random sampling technique, with Class VIII B being the experimental class and Class VIII A being the control class. The tools for this study were quizzes and final tests to understand math concepts. The results showed that comprehension of mathematics concepts was higher among students who learned in Mood, Comprehension, Recall, Digestion, Expansion, and Repetitive Collaborative Learning models than students who learned in conventional learning. Proven to be excellent model. Keywords – Cooperative Learning Model, Mathematical Concept Understanding, MURDER Model.